Analysis of Economic, Social, and Feed Quality Factors of Ration Produced by Small Scale Feed Industry on the Satisfaction of Layer farmers in Sidrap Regency - S. Irmasusanti; A. R. Siregar; St. Rohani; . Isbandi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
This aim of the study was to analyze the influence of economic, social, and feed quality factors on layer farmers’ satisfaction towards the ration produced by small scale feed industry in Sidrap Regency. The study was conducted by survey and observation method. Data were analyzed using the linear regression analysis. The results showed that the economic and feed quality factors did not significantly affect the level of farmers’ satisfaction. However, social factor contributed significantly to the satisfaction of farmer on the ration produced by small scale feed industry